Effect of a Wearable Device-Based Physical Activity Intervention in North Korean Refugees: Pilot Randomized Controlled Trial - Ji Yoon Kim; Kyoung Jin Kim; Kyeong Jin Kim; Jimi Choi; Jinhee Seo; Jung-Been Lee; Jae Hyun Bae; Nam Hoon Kim; Hee Young Kim; Soo-Kyung Lee; Sin Gon Kim (JMIR Publications, 2023)
BackgroundEffective health interventions for North Korean refugees vulnerable to metabolic disorders are currently unelucidated. ObjectiveThis study aimed to evaluate the effects of digital health interventions in North Korean refugees using a wearable activity tracker (Fitbit device). MethodsWe conducted a prospective, randomized, open-label study on North Korean refugees aged 19-59 years between June 2020 and October 2021 with a 12-week follow-up period. The participants were randomly assigned to either an intervention group or a control group in a 1:1 ratio. The intervention group received individualized health counseling based on Fitbit data every 4 weeks, whereas the control group wore the Fitbit device but did not receive individualized counseling. The primary and secondary outcomes were the change in the mean daily step count and changes in the metabolic parameters, respectively. ResultsThe trial was completed by 52 North Korean refugees, of whom 27 and 25 were in the intervention and control groups, respectively. The mean age was 43 (SD 10) years, and 41 (78.8%) participants were women. Most participants (44/52, 95.7%) had a low socioeconomic status. After the intervention, the daily step count in the intervention group increased, whereas that in the control group decreased. However, there were no significant differences between the 2 groups (+83 and -521 steps in the intervention and control groups, respectively; P=.500). The effects of the intervention were more prominent in the participants with a lower-than-average daily step count at baseline (<11,667 steps/day). After the 12-week study period, 85.7% (12/14) and 46.7% (7/15) of the participants in the intervention and control groups, respectively, had an increased daily step count (P=.05). The intervention prevented the worsening of the metabolic parameters, including BMI, waist circumference, fasting blood glucose level, and glycated hemoglobin level, during the study period. ConclusionsThe wearable device-based physical activity intervention did not significantly increase the average daily step count in the North Korean refugees in this study. However, the intervention was effective among the North Korean refugees with a lower-than-average daily step count; therefore, a large-scale, long-term study of this intervention type in an underserved population is warranted. Trial RegistrationClinical Research Information Service KCT0007999; https://cris.nih.go.kr/cris/search/detailSearch.do/23622